Legal embedment of children’s participatory rights in the Czech legal code - Borská, Jana; Švejdarová, Sylva (Journal of nursing, social studies and public health, 2016)
In the past three years, the Czech Republic has made far-reaching interferences in the legal regulation of socio-legal protection of children. In particular, children’s rights have been strengthened, and new legal means assisting their protection have been established. With the adoption of new legal regulation of family law (which is comprehensively regulated by the Civil Code Act No. 89/2012 Coll.), a new procedural regulation has also followed, which deals with procedural ordinances connected with the protection of minor children, and a new act on special court procedures has been adopted. This extensive legal regulation has been a reaction to the elevated need of child protection, the necessity of which was evident in the periodical evaluations of the reports on the implementation of the Convention on Children’s Rights in the Czech Republic. The increased children’s rights protection, including the participatory right, was implemented in the new legislation, which became binding on 1 January, 2014. The purpose of this paper is to define the implementation of the children’s participatory right into the new legal regulation in the Czech legal code, with a focus on the connection between such legal regulations, regarding the socio-legal children’s rights protection authority (SLCRPA), and the courts in civil procedures, with respect to the differing roles and positions of the SLCRPA and courts in guaranteeing child protection. We have carried out a comparative analysis of legal texts from the point of view of implementation of international documents. The examined home legislation included the Act No. 359/1999 Coll., on Socio-Legal Child Protection, Act No. 89/2012 Coll., the Civil Code, Act No. 99/1963 Coll., the Civil Proceedings Code, Act No. 292/2013 Coll., on Special Court Procedures and the practical impact of such legislative regulation.
Keywords: Child; Child Advocacy; zákonodárství jako téma; Legislation as Topic; ochrana práv dítěte; Česká republika; sociální práce; dítě; Social Work; Czech Republic